Exploring the CD3/CD56/TNF-α/Caspase3 pathway in pyrethroid-induced immune dysregulation: curcumin-loaded chitosan nanoparticle intervention - Nawal Alsubaie; Yasmina M. Abd-Elhakim; Amany Abdel-Rahman Mohamed; Tarek Khamis; Tarek Khamis; Mohamed M. M. Metwally; Mohamed M. M. Metwally; Nawal Helmi; Afnan M. Alnajeebi; Badriyah S. Alotaibi; Amirah Albaqami; Wedad Mawkili; et al. (Frontiers in Pharmacology)
IntroductionConflict reports exist on the impact of pyrethroid insecticides on immune function and the probable underlying mechanisms.MethodsThis study evaluated the effect of an extensively used pyrethroid insecticide, fenpropathrin (FTN) (15 mg/kg b.wt), on the innate and humoral immune components, blood cells, splenic oxidative status, and mRNA expression of CD3, CD20, CD56, CD8, CD4, IL-6, TNF-α, and Caspase3 in a 60-day trial in rats. Besides, the possible defensive effect of curcumin-loaded chitosan nanoparticle (CML-CNP) (50 mg/kg b.wt) was evaluated.ResultsFTN exposure resulted in hypochromic normocytic anemia, thrombocytosis, leukocytosis, and lymphopenia. Besides, a significant reduction in IgG, not IgM, but increased C3 serum levels was evident in the FTN-exposed rats. Moreover, their splenic tissues displayed a substantial increase in the ROS, MDA, IL-6, and IL-1β content, altered splenic histology, and reduced GPX, GSH, and GSH/GSSG. Furthermore, a substantial upregulation of mRNA expression of splenic CD20, CD56, CD8, CD4, CD3, IL-6, and TNF-α, but downregulation of CD8 was detected in FTN-exposed rats. FTN exposure significantly upregulated splenic Caspase-3 and increased its immunohistochemical expression, along with elevated TNF-α immunoexpression. However, the alterations in immune function, splenic antioxidant status, blood cell populations, and immune-related gene expression were notably restored in the FTN + CML-CNP-treated group.ConclusionThe findings of this study highlighted the immunosuppressive effects of FTN and suggested the involvement of many CD cell markers as a potential underlying mechanism. Additionally, the results demonstrated the effectiveness of CML-CNP in mitigating pollutant-induced immune disorders.